Evidence-Based Case Report: Comparison of Potassium Competitive Acid Blocker and Proton Pump Inhibitor as First Line Therapy in Adult Patients with H. pylori Infection - Mustikarani, Dewi; Citrawijaya, Henrico; Nursyirwan, Saskia Aziza (The Indonesian Society for Digestive Endoscopy, 2024)
ABSTRACTBackground: Increased eradication of Helicobacter pylori decreases the incidence of gastric cancer. Vonoprazan is a potassium-competitive acid blocker (PCAB) with a stronger acid production suppression effect than proton pump inhibitors (PPI). Vonoprazan has been recognized as a therapy for gastric acid reflux disease since 2015 in Japan, but the comparison of the effectiveness of PCAB first-line therapy with PPI for adult patients with H. pylori infection is still controversial.Method: A literature search was carried out on three databases: Pubmed, Cochrane, and Scopus on March 30th 2023, using keywords vonoprazan, potassium competitive acid blocker (PCAB), proton pump inhibitor, and H. pylori. There were 7 studies on Pubmed, 26 studies on Cochrane, and 144 studies on Scopus. Critical screening was conducted using the Oxford Centre for Evidence-Based Medicine for systematic reviews and randomized controlled trials. Results: Based on screening of inclusion and exclusion criteria, one study met the criteria. The intention to treat analysis (ITT) showed eradication of H. pylori in the combination of three therapies with PCAB vs PPI of 91.81% vs 75.5% (1,18 [1.08−1.28], p0,0001), no heterogeneity found (I2 = 43%). Analysis per protocol showed PCAB versus PPI eradications of 92.99% vs 78.57% (1,13 [1,02−1,26], p = 0.02), heterogeneity obtained (I 2 = 75%). Conclusion: Generally, PCAB has better eradication than PPI as first-line therapy for adult patients with H. pylori infection Keywords: potassium competitive acid blocker, proton pump inhibitors, helicobacter pylori